2022
DOI: 10.1111/appy.12518
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year community program in Singapore to prevent cognitive decline

Abstract: Introduction: There is a scarcity of naturalistic follow-up studies on cognitive stimulating activities (CSAs), particularly in a real-world setting and over long-term.We thus investigated a pooled novel CSA intervention to prevent cognitive decline amongst community-dwelling older adults without dementia.Methods: Nested within a community-based longitudinal follow-up cohort study of community-dwelling and multi-ethnic older adults (N = 991), a subset of the cohort (n = 264) underwent four single-blinded rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lastly, we hypothesized that 4) participants who had been involved in NPIs from the CHI study would be likely to retain or show improvement in cognitive function and psychosocial outcomes when assessed during the LFC study. In support of this hypothesis, Ng et al conducted a 5-year follow up and found that participants who had previously participated in NPIs had cognitive improvements as compared to control participants who did not participate in NPIs [16] . As such, the effects from previous NPIs should be retained when examined in the LFC Study.…”
Section: Research Hypothesesmentioning
confidence: 96%
“…Lastly, we hypothesized that 4) participants who had been involved in NPIs from the CHI study would be likely to retain or show improvement in cognitive function and psychosocial outcomes when assessed during the LFC study. In support of this hypothesis, Ng et al conducted a 5-year follow up and found that participants who had previously participated in NPIs had cognitive improvements as compared to control participants who did not participate in NPIs [16] . As such, the effects from previous NPIs should be retained when examined in the LFC Study.…”
Section: Research Hypothesesmentioning
confidence: 96%
“…Aging is an increasingly important concern around the globe (Bloom et al, 2015;Lenox-Smith et al, 2018), and is accompanied by a combination of cognitive decline (mentioned earlier in this review) and various age-related neurodegenerative disorders and cardiovascular health issues (e.g., Brookmeyer et al, 2007). Therefore, it is critical to invest resources in developing effective non-pharmacological interventions (e.g., Ng et al, 2022) to either help mitigate the rate of cognitive decline or promote cognitive maintenance, so as to reduce economic burdens on society and healthcare institutions. As music is highly accessible and widely available, music-based interventions or music therapy, could be considered as one of the most ideal candidates among current forms of non-pharmacological interventions (Agres et al, 2021).…”
Section: Mitigating Age-related Decline In the Bayesian Brain: Use Of...mentioning
confidence: 98%